Enhanced THz frequency multiplier efficiency by quasi-ballistic electron reflection in double-heterojunction structures - Ong, D. S.; Hartnagel, H. L. (EPL ASSOCIATION, 2008)
A self-consistent ensemble Monte Carlo model is used to demonstrate the enhancement of frequency multiplication efficiency by quasi-ballistic electron reflection (Q-BER) in In(0.52)Al(0.48)As/In(0.53)Ga(0.47)As/In(0.52)Al(0.48)As heterostructures. Simulation results showed that the strong nonlinearity due to this familiar mechanism is able to produce the third harmonic of the current response at almost half of the amplitude of the fundamental at excitation frequencies between 50 and 250 GHz. It is found that the proposed structure is more efficient for frequency multiplication with a thinner well, where the Q-BER phenomenon is more profound. Copyright (C) EPLA, 2008.